Respuesta :
Answer:
Simplifying
3x + 9 = 5x + 21
Reorder the terms:
9 + 3x = 5x + 21
Reorder the terms:
9 + 3x = 21 + 5x
Solving
9 + 3x = 21 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
9 + 3x + -5x = 21 + 5x + -5x
Combine like terms: 3x + -5x = -2x
9 + -2x = 21 + 5x + -5x
Combine like terms: 5x + -5x = 0
9 + -2x = 21 + 0
9 + -2x = 21
Add '-9' to each side of the equation.
9 + -9 + -2x = 21 + -9
Combine like terms: 9 + -9 = 0
0 + -2x = 21 + -9
-2x = 21 + -9
Combine like terms: 21 + -9 = 12
-2x = 12
Divide each side by '-2'.
x = -6
Simplifying
x = -6
God bless you and I hope this helps :)
Simplifying
3x + 9 = 5x + 21
Reorder the terms:
9 + 3x = 5x + 21
Reorder the terms:
9 + 3x = 21 + 5x
Solving
9 + 3x = 21 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
9 + 3x + -5x = 21 + 5x + -5x
Combine like terms: 3x + -5x = -2x
9 + -2x = 21 + 5x + -5x
Combine like terms: 5x + -5x = 0
9 + -2x = 21 + 0
9 + -2x = 21
Add '-9' to each side of the equation.
9 + -9 + -2x = 21 + -9
Combine like terms: 9 + -9 = 0
0 + -2x = 21 + -9
-2x = 21 + -9
Combine like terms: 21 + -9 = 12
-2x = 12
Divide each side by '-2'.
x = -6
Simplifying
x = -6
God bless you and I hope this helps :)
Answer:
X = -6
1. 3x + 9 = 5x + 21
2. Subtract -5x from both sides
3x + 9 - 5x = 5x + 21 - 5x
3.-2x + 9 = 21
4. Subtract 9 from both sides
-2x + 9 - 9 = 21 - 9
5.-2x = 12
6. Divide both sides by -2
-2x/-2 = 12/-2
7. x= -6